Knowledge and Adoption of Bt Cotton Cultivation Practices - H. D. Rajput; Umesh R. Chinchmalatpure (Indian Journal of Extension Education, 2016)
The present study was conducted in Jalgaon and Dhule district of North Maharashtra, with a random sample of 175 Bt cotton growers, to measure the level of knowledge of Bt cotton growers and to understand the relationship between selected characteristics of Bt cotton growers and their extent of adoption. The results indicate that majority of the respondents had medium (53.71 per cent) level of adoption towards cultivation practices of Bt cotton. The analysis of correlation revealed that variables viz., education, area under Bt cotton, annual income, socio-economic status, social participation, scientific orientation, cosmopoliteness, extension contact and knowledge had positive and significant influence on their level of knowledge.